Review of the civil administration of Mesopotamia - Wilson, Arnold Talbot, Sir, 1884-1940; Bell, Gertrude Lowthian, 1868-1926 (Cmd. (Great Britain. Parliament), 1920)
"This paper gives an account of the Civil Administrator of Mesopotamia during the British military occupation, that is to say, down to the summer of the present year [1920] when, a mandate for Mesopotamia having been accepted by Great Britain, steps were being taken for the early establishment of an Arab government. His Majesty's government called for a report on this difficult period from the acting Civil Commissioner, who entrusted the preparation of it to Miss Gertrude L. Bell, C.B.E. India Office, 3rd December 1920."